Maximum in the middle: nonlinear response of microbial plankton to ultraviolet radiation and phosphorus. - Juan Manuel Medina-Sánchez (Public Library of Science (PLoS), 2013)
The responses of heterotrophic microbial food webs (HMFW) to the joint action of abiotic stressors related to global change have been studied in an oligotrophic high-mountain lake. A 2×5 factorial design field experiment performed with large mesocosms for >2 months was used to quantify the dynamics of the entire HMFW (bacteria, heterotrophic nanoflagellates, ciliates, and viruses) after an experimental P-enrichment gradient which approximated or surpassed current atmospheric P pulses in the presence vs. absence of ultraviolet radiation. HMFW underwent a mid-term (<20 days) acute development following a noticeable unimodal response to P enrichment, which peaked at intermediate P-enrichment levels and, unexpectedly, was more accentuated under ultraviolet radiation. However, after depletion of dissolved inorganic P, the HMFW collapsed and was outcompeted by a low-diversity autotrophic compartment, which constrained the development of HMFW and caused a significant loss of functional biodiversity. The dynamics and relationships among variables, and the response patterns found, suggest the importance of biotic interactions (predation/parasitism and competition) in restricting HMFW development, in contrast to the role of abiotic factors as main drivers of autotrophic compartment. The response of HMFW may contribute to ecosystem resilience by favoring the maintenance of the peculiar paths of energy and nutrient-mobilization in these pristine ecosystems, which are vulnerable to threats by the joint action of abiotic stressors related to global change.